2017
DOI: 10.1080/17461391.2017.1406007
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training but no resistance training increases SIRT3 in skeletal muscle of sedentary obese male adolescents

Abstract: In recent years, prevalence of obesity in children and adolescents has increased. A strategy for prevention and management of obesity is aerobic training (AT) due to its effectiveness to decrease fat mass. AT increases the content of SIRT3, a mitochondrial protein that increases the expression of PGC-1α and NFR1, thereby enhances mitochondrial function and metabolic health. Resistance training (RT) provides metabolic benefits but its effect on SIRT3 content is unknown. To compare the effect of AT and RT on SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…Although the between‐group differences were not significant, our findings are consistent with previous literature. The increase of 3.0 mL/kg/min in VO 2peak in the RDa group is similar to other exercise studies in adolescents with obesity showing increases of 2.7 mL/kg/min 51 and 3.8 mL/kg/min 52 . However, we did demonstrate that the RDa group increased their maximal power output (watts) by week 12, compared to the Con group.…”
Section: Discussionsupporting
confidence: 90%
“…Although the between‐group differences were not significant, our findings are consistent with previous literature. The increase of 3.0 mL/kg/min in VO 2peak in the RDa group is similar to other exercise studies in adolescents with obesity showing increases of 2.7 mL/kg/min 51 and 3.8 mL/kg/min 52 . However, we did demonstrate that the RDa group increased their maximal power output (watts) by week 12, compared to the Con group.…”
Section: Discussionsupporting
confidence: 90%
“…The SIRT3 remained unchanged, suggesting that this protein might not be activated during resistance training because this type of training preferentially uses phosphocreatine and muscle glycogen for ATP synthesis in the sarcoplasm. This means that resistance training does not induce sufficient metabolic stress to activate oxidative phosphorylation, and consequently, the metabolic pathways that induce the activation of SIRT3 [37]. Other authors have reported that AMPKα2 activity increases immediately after an acute load of resistance exercise, however, after 2 h this effect decreases [52] and is possibly insufficient to activate the AMPK-PGC-1α-SIRT3 axis.…”
Section: Effects Of Different Type Of Exercise On the Sirtuins In mentioning
confidence: 99%
“…NAMPT levels correlated positively with PGC-1α expression, mitochondrial content, maximal mitochondrial ATP synthesis in skeletal muscle and overall maximal aerobic capacity [48]. Concordantly, increased skeletal muscle SIRT3 content and PGC-1α expression were reported in men who were sedentary obese at baseline after a 12 week aerobic exercise intervention [49]. In a 6 week one-leg endurance exercise intervention, NAMPT protein levels only increased in the trained leg as compared with the untrained leg [34], further supporting the paradigm of activating the NAD + /SIRT axis through exercise and NAMPT induction.…”
Section: How To Boost Nad+ In Humans?mentioning
confidence: 99%